The Implementation of Education for Sustainable Development-Oriented Problem-Based Learning in Practical Work for Making Alum - Resi Pratiwi; Hanifah Setiowati (Chemistry Education Department, 2022)
The problem-based learning (PBL) method is one method to insert the competency targets of Education for Sustainable Development (ESD). This research aims to investigate how the implementation of ESD-oriented problem-based learning to metal and non-metal chemistry practical work. The research method used in this research is a qualitative descriptive method and the research subject is the 4th-semester Chemistry Education university students. The research result shows that the ESD-oriented PBL method is applicable in metal and non-metal chemistry practical work. Practical work with the ESD-oriented PBL method can be used as an innovation for practical learning activities to achieve the ESD target competencies. Based on the questionnaires responded by the students, it can be concluded that the practical work with the ESD-oriented PBL method could increase the students’ ability for problem-solving with percentages of 33% strongly agree and 50% agree. Practical work learning with the ESD-oriented PBL affects the students to be more active in practical work activities. The stages of the PBL method help the students develop problem-solving abilities, and this is one target of ESD competencies.